Reimagining Democracy: An Exploration of Anies Baswedan's "Desak Anies" Program - Maspul, Kurniawan Arif (Indonesian Journal of Social Development, 2024)
Global democracy is at a crossroads, amidst geopolitical turmoil and socioeconomic upheaval. Despite widespread support for democratic principles such as popular sovereignty and civic involvement, their practical implementation is frequently hampered by entrenched power dynamics and vested interests. Anies Baswedan's pioneering "Desak Anies" program in Indonesia takes a novel approach to democratic government, questioning traditional top-down methods and calling for active citizen participation in decision-making processes. This study, based on theoretical frameworks proposed by authors such as Dahl and Rousseau, investigates the Desak Anies initiative's complex impact. The study's qualitative research approaches, which include a literature review and content analysis observations, aim to provide thorough insights into Desak Anies' transformative potential in transforming democratic behaviors. The findings show that Desak Anies had a significant impact on youth empowerment, instilling a sense of agency and political efficacy in young Indonesians. Furthermore, the program has made a substantial contribution to improving community cohesiveness by giving a forum for varied views to be heard and respected. Desak Anies has ushered in a new era of governmental openness, with an emphasis on open data projects and citizen involvement, which promote accountability and trust in government institutions; establishes a new benchmark for democratic renewal and sustainability by leveraging grassroots mobilization and adopting inclusive policies, providing a replicable model for advancing democracy and fostering inclusive government on a global scale.